2022
DOI: 10.5194/acp-22-8935-2022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trend of ozone pollution in China during 2014–2020: distinct seasonal and spatial characteristics and ozone sensitivity

Abstract: Abstract. In the past decade, ozone (O3) pollution has become a severe environmental problem in China's major cities. Here, based on available observational records, we investigated the long-term trend of O3 pollution in China during 2014–2020. The O3 concentrations were slightly higher in urban areas than in non-urban areas. During these 7 years, the highest O3 concentrations primarily occurred during summer in northern China, and during autumn or spring in southern China. Although O3 precursors, including ni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 84 publications
(86 reference statements)
3
34
0
Order By: Relevance
“…Currently, the VOC-limited regime exists in most major urban clusters in China, which are also areas with high ozone levels. The exploration of the causes of ozone rise in China illustrates the current need for VOC control, which is consistent with the findings of previous studies on major cities and city clusters (Wang et al, 2022;Yang et al, 2019). Appropriate reduction ratios of VOC and NO x emission can control both PM 2.5 and O 3 pollution, which is suggested by the simultaneous decline in O 3 and PM 2.5 concentrations in Beijing in recent years (Ren et al, 2021).…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…Currently, the VOC-limited regime exists in most major urban clusters in China, which are also areas with high ozone levels. The exploration of the causes of ozone rise in China illustrates the current need for VOC control, which is consistent with the findings of previous studies on major cities and city clusters (Wang et al, 2022;Yang et al, 2019). Appropriate reduction ratios of VOC and NO x emission can control both PM 2.5 and O 3 pollution, which is suggested by the simultaneous decline in O 3 and PM 2.5 concentrations in Beijing in recent years (Ren et al, 2021).…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…In fact, some observational studies have illustrated the hygroscopic capacity of the aged secondary OA (Hong et al., 2018; Kuang et al., 2020; Xu et al., 2020). Unlike the strong reduction of primary aerosols, there is evidence suggesting the enhancement of secondary aerosol formation in winter due to the rising atmospheric oxidizing capacity (Wang, Gao, et al., 2022; Wang, Parrish, et al., 2022). If this is the case for secondary OA, a consideration of its hygroscopicity would imply an additional offset on the AOD decline effect from PM 2.5 reduction in winter.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Earlier worsening ozone pollution, from 2013 to 2017, have been attributed to ozone's nonlinear response to large reductions in nitrogen oxides (NO x ) emissions without equivalent reductions in volatile organic compounds (VOCs) emissions (Y. Liu & Wang, 2020b; N. Wang et al., 2019; T. Wang et al., 2017), particularly in many urban regions that were within the NO x ‐saturated regime (H. Lu et al., 2019; Ou et al., 2016). Nevertheless, with the continuous reductions in NO x , the sensitivity of summertime ozone production to VOCs in some urban areas of China may have gradually weakened (W. Wang et al., 2021, 2022). Furthermore, it has been suggested that the turning point between NO x ‐saturated and NO x ‐limited regimes in some densely populated urban areas of China was reached in 2019 (Chen et al., 2021).…”
Section: Introductionmentioning
confidence: 99%